TRANSFORMATION OF EDUCATION QUALITY BASED ON EDUCATION REPORT CARD: LONGITUDINAL INPUT-PROCESS-OUTPUT (IPO) ANALYSIS IN JUNIOR HIGH SCHOOL - Rosalia Kharisma; Syamsuri Syamsuri; Achmadi Achmadi (Journal of Language and Literature Education, 2026)
This study aims to analyze the transformation of educational quality based on the Education Report through a longitudinal Input–Process–Output (IPO) framework and to formulate a Four-Phase Educational Quality Transformation Model at SMP Negeri 4 Rasau Jaya during the 2021–2025 period. The research employed a descriptive-analytical longitudinal design using secondary data obtained from the Education Report platform. Data were analyzed through document analysis, longitudinal trend analysis, annual percentage change, cumulative growth analysis, exploratory correlation analysis, and cross-dimensional linkage analysis within the IPO framework. The findings indicate that educational quality transformation occurred progressively and non-linearly through four phases: recovery, strengthening, stabilization, and acceleration. Significant improvements were observed in literacy (from 25.00 to 83.33; cumulative growth of 233.3%), numeracy (from 34.38 to 80.00; cumulative growth of 132.7%), teacher reflection (49.3%), and learning quality. Correlation analysis revealed a very strong relationship between the input and process dimensions (r = 0.92), while the relationships between process and output (r = 0.30) and input and output (r = 0.33) were relatively low, indicating a time-lag effect in translating institutional improvements into student outcomes. In conclusion, the proposed Four-Phase Educational Quality Transformation Model extends the conventional IPO framework by incorporating a longitudinal perspective, demonstrating that sustainable educational quality improvement is achieved through cumulative enhancement of teacher capacity, school governance, and learning processes over time rather than through short-term interventions